ISLAMIC ECONOMICS AND PARTIAL–TOTAL RELIGIOSITY: A Case Study of Majlis Taklim in Banjarmasin - Hidayatullah, Muhammad Syarif (Islamuna: Jurnal Studi Islam, 2020)
In Banjarmasin, most of majlis taklim are dominated by the study of sufism. If there is a discussion of fiqh (Islamic jurisprudence), it is more inclined about fiqh al-‘ibâdah (fiqh of worship). Meanwhile fiqh al-mu‘âmalah (fiqh of social interaction) is not a study that is considered important, so that the majlis taklim by the study fiqh al-mu‘âmalah are few. Based on participant observation, there are two majlis taklims who carry out da’wa of islamic economics through the study fiqh al-mu‘âmalah, they are Darul Ma‘arif and Ar-Rahmat. Using interactive data analysis, this field research indicates that the two majlis taklims carry out da‘wa of islamic economics by presenting fiqh al-mu‘âmalah contemporary material through a discussion of mu‘âmalah which is associated by economic issues and modern financial. Considering that study fiqh al-mu‘âmalah is still few, it is necessary to initiate transformative da‘wa as an effort to build a comprehensive Islamic paradigm including worship and social interaction, so that the partial religiousity phenomenon in Banjarmasin become a total religiousity. [Majlis taklim di Kota Banjarmasin didominasi materi pengajian sufism. Jika ada pembahasan fikih, ia lebih cenderung kepada pembahasan fikih ibadah. Sedangkan fikih muamalah tidak menjadi kajian yang dianggap penting, sehingga majlis taklim dengan kajian fikih muamalah (fikih ekonomi syariah) terbatas. Berdasarkan observasi partisipan, ada dua majlis taklim yang melaksanakan dakwah ekonomi syariah melalui pengajian fikih muamalah, yaitu Majlis Taklim Darul Ma‘arif dan Majlis Taklim Ar-Rahmat. Penelitian lapangan yang menggunakan analisis data interaktif ini menunjukkan bahwa dua majlis taklim tersebut melaksanakan dakwah ekonomi syariah dengan penyajian materi fikih muamalah kontemporer melalui pembahasan muamalah yang dikaitkan dengan isu-isu ekonomi dan keuangan modern. Karena pengajian fikih muamalah masih sedikit, dakwah transformatif perlu digagas sebagai upaya membangun paradigma Islam komprehensif yang mencakup ibadah dan muamalah, sehingga fenomena religiusitas parsial di Banjarmasin berubah menjadi religiusitas total]